Arbuscular mycorrhiza in Colombian coffee plantations fertilized with coffee pulps as organic manure - Raul Posada (Journal of Applied Botany and Food Quality, 2014)
The distribution of arbuscular mycorrhizal (AM) fungal structures in roots, in soil surrounding roots and in amended coffee pulps (CP) was investigated in 12 coffee plantations in Colombia. Fresh CP had been added to plants 6-10 months before sampling. The questions were whether soil chemical and physical parameter and soil depth had an effect on mycorrhiza. Root colonization rates with AM increased in CP amended-plants (F=7.75, P< 0.001) as compared to a non-amended control. Significantly more roots, CP and AM root colonization were found in the upper soil layer (F= 41.24, 9.54, 6.60 respectively, P< 0.001), while root external mycelium and CP colonization with AM were not affected by soil depth (F= 14.82, P> 0.05). External mycelium length differed between locations (F= 5.89, P< 0.001) and was inversely correlated with soil water content (r= -0.655, P= 0.02). External mycelium length per AM colonized root was higher in the lower soil layer (F=14.82, P< 0.05). Soil aeration seemed to be an important physical characteristic for mycorrhiza development in and around coffee roots. Higher mycorrhiza colonization in CP amended-plants might be an adaptive strategy for nutrients acquisition, and AM external mycelium that colonizes CP might take up nutrients directly during CP decomposition.